Variation in The Body Composition in Pre-Menopausal & Post-Menopausal Women (Bangladesh Medical Journal, 2014)
Menopause is an important hallmark for women because lots of changes occur in the body secondarily due to diminished ovarian function. This comparison study was carried out in the Department of Physical medicine and rehabilitation, Bangabandhu Sheikh Mujib Medical University to describe the variation of body composition and to observe the variation of body density, fat deposition among pre and post menopausal women. For this 50 patients of Pre menopausal and post menopausal women aged from 35 to 55 years were taken in this study. The average duration of which was 6 months. The patients were selected on the basis of inclusion and exclusion criteria. Main outcome measures were mean value of height, weight and age of menarch, body mass index, total fat mass amount, percentage of body fat(%), lean mass amount( kg), lumbar spine BMD, waist to hip ratio. Mean values of body mass index, total fat mass amount, percentage of body fat (%), lean mass amount (kg), lumbar spine BMD, waist measurement, hip measurement, waist to hip ratio were higher in pre menopausal group than post menopausal group. The study concluded that bone mineral density is greater in pre-menopausal women than post-menopausal women and remains high up to 35-40 years of age, and declines to older age. BMD positively correlates with weight of women. Premenopausal women have higher height than postmenopausal women though height does not have correlation with BMD in this study. DOI: http://dx.doi.org/10.3329/bmj.v41i3.18957 Bangladesh Medical Journal 2012 Vol.41(3): 38-41